Secure data stream outsourcing with publicly verifiable integrity in cloud storage. (December 2019) - Wu, Qiyu; Zhou, Fucai; Xu, Jian; Wang, Qiang
Abstract: Recent technological developments in Internet of Things has led to enormous amount of data stream. Limited by storage and computation capabilities, increasing companies and individuals outsource their data stream to powerful cloud servers, from which they can query the data when it is needed. Nevertheless, it presents a challenge in order to ensure the cloud server can comply with their advertised policies and return the correct query results. In this paper, we focus in particular on the scenario where a data owner wishes to (i) outsource its unbounded data stream to a cloud server; (ii) enable anyone who has the public key to retrieve the outsourced data stream; (iii) ensure public verification of the integrity for query results. To this end, we propose a secure data stream outsourcing scheme with publicly verifiable integrity in cloud storage (DSO-PVI), which builds upon the well-established techniques of Chameleon Vector Commitment (CVC) to guarantee the integrity of query results. Moreover, we introduce a formal security model of DSO-PVI and prove that it is secure against malicious cloud servers. Our analyses and experimental results demonstrate that the proposed scheme is greatly improved in terms of functionality and performance.